Improvement Of Medical Product Through Design For Environment (DfE) Methodology : A Case Study Dialyzer - Mohd Hafiz , Mohd Ismail (UTeM, 2010)
Design for environment is such an important methodology in discovering the new product environment that is equivalent in order to fulfill the customers’ needs and wants. The development of medical product followed by proper design such as considering on the design for environment can save both environmental and financial resources. This report proposes the application of principle of Design for Environment (DFE) towards developing a sustainable product. This concept is applied to consider the environmental aspects at all stages of the product development process as well as to increase resources efficiency at all stages of product life cycle ranging from extraction of its material, manufacturing, packaging, transportation, product usage, and finally to recycling or disposal of the product. The aims of this report are to strive for products which causes the lowest possible environmental impact throughout the product life cycle. The methodology carried out in this report is through analyzing an existing medical product and implementing DFE tools and guidelines to design a new sustainable product. A sustainability analysis is conducted concurrently with SolidWorks 2010, to evaluates the environmental impact of a material throughout the life cycle of a product. Based on the evaluation of result from sustainable analysis, a new sustainable material of product was replaced to reduce effect to environment. Lastly, the evaluation and comparison of environment impact and human health of the existing product and sustainable redesign product is carried out with the life cycle assessment (LCA) method. The environment impact is analyzed by mean of SimaPro software which is one of the LCA tools.